Does tourism boost criminal activity?: evidence from a top touristic country - Montolio, Daniel (Crime & delinquency, 2016)
The growth in the number of tourist arrivals in Spain in recent years has had significant economic repercussions; yet, little has been reported about its negative impact. This study goes some way to rectifying this by estimating the impact of tourist activity on crime rates in the Spanish provinces during the period 2000-2008. We use both 2-SLS and GMM techniques in a panel data framework to overcome the various challenges posed by estimating this relationship, namely, controlling for the unobserved characteristics of the provinces, and accounting for both the possible endogeneity of the tourist variable and the inertia of criminal activities. The results show that tourist arrivals have a positive and significant impact on crimes against both property and the person.